2008
DOI: 10.1590/s0100-879x2008000700010
|View full text |Cite
|
Sign up to set email alerts
|

Association of loss of heterozygosity with cytogenetic abnormalities in acute myeloid leukemia and myelodysplastic syndrome

Abstract: Deletions on chromosomes 5 and 7 are frequently seen in myelodysplastic syndrome (MDS) and acute myeloid leukemia (AML). It is assumed that these deletions indicate loss of tumor suppressor genes on these chromosomes and until these tumor suppressor genes are identified, the functional consequences of these deletions and the molecular basis of these myeloid disorders cannot be completely understood. We evaluated loss of heterozygosity (LOH) in 44 patients (18 MDS and 26 AML, diagnosed according to WHO classifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
0
1
Order By: Relevance
“…Meanwhile, there were some differences between the chromosome abnormalities (+8, -8, -20, 20q-, -Y, -7, 5q-) in this study and those of previous studies ( 18 - 20 , 33 ). Among them, the deletion of chromosome 8 (-8) was not found in the studies by Blau et al ( 20 , 33 ) and Pinheiro et al ( 34 ), but it was identified in the studies by Flores-Figueroa et al ( 12 , 19 ) and our study. These inconsistent results may be attributed to the different detection methods (Song et al ( 18 ), Flores-Figueroa et al ( 12 , 19 ), and Pinheiro et al ( 34 ): trypsine-giemsa banding) or to the different populations (Flores-Figueroa et al ( 12 , 19 ): Mexico; Blau et al ( 20 , 33 ): Germany; Pinheiro et al ( 34 ): Brazil).…”
Section: Discussioncontrasting
confidence: 50%
“…Meanwhile, there were some differences between the chromosome abnormalities (+8, -8, -20, 20q-, -Y, -7, 5q-) in this study and those of previous studies ( 18 - 20 , 33 ). Among them, the deletion of chromosome 8 (-8) was not found in the studies by Blau et al ( 20 , 33 ) and Pinheiro et al ( 34 ), but it was identified in the studies by Flores-Figueroa et al ( 12 , 19 ) and our study. These inconsistent results may be attributed to the different detection methods (Song et al ( 18 ), Flores-Figueroa et al ( 12 , 19 ), and Pinheiro et al ( 34 ): trypsine-giemsa banding) or to the different populations (Flores-Figueroa et al ( 12 , 19 ): Mexico; Blau et al ( 20 , 33 ): Germany; Pinheiro et al ( 34 ): Brazil).…”
Section: Discussioncontrasting
confidence: 50%